Communication ability and related factors in children with hearing aids - W. Wijana; Rico Doloksaribu (PERHATI-KL, 2019)
Background:Hearing function is very significant in the development of speech and language. Hearing disorders in children can lead to communication skill disturbance. Hearing aids can help to support the development of hearing, talking, and communication abilities. Several factors such as age, duration of using hearing aids, and parental participation in encouraging children to communicate and undergo auditory verbal therapy, are recognized to have impacts on communication skills. Aim:To find out communication capabilities and related factors after using hearing aids in children. Method:A cross sectional study was performed at a private hearing center in Bandung. Inclusion criteria was children using hearing aids who were doing follow-up in the period January-May 2018. Result: From 60 research subjects, there were 35 (58.33%) who used mixed communication, and 23 (38.33%) were in special school. There were 37 (61.67%) who had more than 6 hours communication, 45 (75%) underwent routine therapy, and 23 (38.33%) underwent Auditory Verbal Therapy (AVT) and Speech Therapy. The assessment was using PEACH (Parents’ Evaluation of Aural/oral performance of Children) score. A total of 66.67% subjects had a low (<60) PEACH score, 16.67% had a moderate (>60 - ≤75) PEACH score, and 16.66% had a normal (>75) PEACH score. The PEACH score in this study showed an average value of 52.63% with 16.66% had a normal (>75) PEACH score. Conclusion:Specific characters that had significant correlation with normal PEACH score were communication method, educational method, communication duration, frequency of therapy, and type of therapy (p <0.05). Keywords: PEACH score, hearing aid, communication, children ABSTRACT Latar Belakang: Fungsi pendengaran sangat berpengaruh pada perkembangan bicara dan bahasa. Gangguan pendengaran pada anak dapat menyebabkan gangguan komunikasi. Alat bantu dengar menunjang mengembangkan kemampuan mendengar, berbicara, dan berkomunikasi. Beberapa faktor seperti usia, lamanya penggunaan alat bantu dengar, dan keaktifan orang tua dalam mendorong anak untuk berkomunikasi dan melakukan terapi verbal pendengaran diketahui memiliki dampak pada keterampilan komunikasi. Tujuan: Mengetahui kemampuan komunikasi dan faktor yang memengaruhi setelah menggunakan alat bantu dengar pada anak-anak. Metode: Telah dilakukan penelitian cross sectional di sebuah Klinik Pusat pendengaran di Bandung pada periode Januari-Mei 2018 . Kriteria inklusi untuk penelitian ini adalah anak yang menggunakan alat bantu dengar, yang melakukan kontrol pada periode Januari-Mei 2018. Hasil: Dari 60 subjek yang sesuai dengan kriteria penelitian, terdapat 35 anak (58,33%) yang menggunakan komunikasi campuran, dan 23 anak (38,33%) mengikuti pendidikan di sekolah khusus. Ada 37 anak (61,67%) yang memiliki durasi komunikasi lebih dari 6 jam, 45 anak (75%) rutin dalam terapi, dan 23 anak (38,33%) yang menggunakan terapi Auditory Verbal Therapy (AVT) dan terapi wicara. Penilaiannya menggunakan skor PEACH (Parents’ Evaluation of Aural/ oral performance of Children). Sebanyak 66,67% subjek memiliki skor PEACH rendah (<60), 16,67% memiliki skor PEACH sedang (> 60 - ≤ 75), dan 16,66% memiliki skor PEACH normal (> 75). Skor PEACH dalam penelitian ini menunjukkan nilai rata-rata 52,63% dengan 16,66% memiliki skor PEACH normal (>75). Kesimpulan: Karakteristik yang memiliki hubungan yang signifikan dengan skor PEACH normal adalah metode komunikasi, metode pendidikan, durasi komunikasi, frekuensi terapi, dan jenis terapi yang digunakan (p<0,05).